2002
DOI: 10.1017/s0033291702006657
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive deficits in decision-making and planning of patients with DSM-III-R borderline personality disorder

Abstract: These findings suggest that BPD is associated with complex impairments in dissociable cognitive processes mediated by circuitry encompassing the frontal lobes. These impairments may mediate some of the behavioural changes evident in BPD. Further work is needed to examine the specificity of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
6
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 29 publications
12
123
6
11
Order By: Relevance
“…Decision making has been a research target in substance and alcohol misuse disorders (Bechara et al, 2001;Ersche et al, 2008;Rogers et al, 1999b;Rogers and Robbins, 2001), unipolar depression and bipolar disorder (Chandler et al, 2009;Murphy et al, 2001), suicidaility (Dombrovski et al, 2010;Jollant et al, 2005), and impulsive personality disorders (Bazanis et al, 2002;Kirkpatrick et al, 2007). Adjunctive work has explored the idea that impairments in decision making can serve as markers for likely relapse (Adinoff et al, 2007;Bechara et al, 2001) and facilitate the exploration of therapeutic interventions (Rahman et al, 2006;Robbins and Arnsten, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Decision making has been a research target in substance and alcohol misuse disorders (Bechara et al, 2001;Ersche et al, 2008;Rogers et al, 1999b;Rogers and Robbins, 2001), unipolar depression and bipolar disorder (Chandler et al, 2009;Murphy et al, 2001), suicidaility (Dombrovski et al, 2010;Jollant et al, 2005), and impulsive personality disorders (Bazanis et al, 2002;Kirkpatrick et al, 2007). Adjunctive work has explored the idea that impairments in decision making can serve as markers for likely relapse (Adinoff et al, 2007;Bechara et al, 2001) and facilitate the exploration of therapeutic interventions (Rahman et al, 2006;Robbins and Arnsten, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One way to meet this challenge will be to integrate properly different kinds of methodologies in order to establish how cognitive deficits in these disorders interact with other aspects of their pathophysiology. For example, recent research has suggested that altering 5-HT function in healthy volunteers can alter performance of the decision-making task used in Bazanis et al (2002). Since there is now increasing evidence that 5-HT function is compromised in borderline PD (including the neuromodualtion of the prefrontal cortex ; Soloff et al 2000), we can test the hypothesis that the impaired decisionmaking associated with borderline PD involves altered neuromodulation of cognitive processes mediated by the prefrontal cortex.…”
Section: Resultsmentioning
confidence: 98%
“…De nombreux auteurs soutiennent que les troubles de personnalité du DSM-IV sont en fait des manifestations d'altérations du fonctionnement exécutif (Bazanis et al, 2002 ;Kunert, 2003 ;Coolidge et al, 2004 ;Lenzenweger et al, 2004 ;Travers et King, 2005). Le terme de fonctions exécutives réfère au fait que les régions frontales et pré frontales du cerveau constituent le substrat neuroanatomique d'un en semble de fonctions qualifiées d'exécutives qui permettent l'organi sation, la planification, la flexibilité, l'abstraction et l'autocontrôle (Tableau 1).…”
Section: Déficits Des Fonctions Exécutives Chez Les Patients Avec Un Tplunclassified
“…Swirsky-Sacchetti et al (1993) obtiennent par ailleurs des résultats qui montrent une susceptibilité accrue à l'interférence en plus d'atteintes aux habiletés motrices, une pauvre mémoire non verbale et une difficulté d'intégration visuomotrice complexe chez les patients avec un TPL. Bazanis et al (2002) ont observé des atteintes significatives lors de tests exécutifs qui impliquent la prise de décision et la planification. Soulignons que ces auteurs ont choisi des tâches particulièrement associées aux aires orbitofrontales mais non pas aux aires dorsolatérales et dorsomédianes.…”
Section: Survol De La Recherche Sur Les Fonctions Exécutives Des Persunclassified